2003
DOI: 10.1111/j.0014-3820.2003.tb00216.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Structure of Age Classes in Camellia Japonica (Theaceae)

Abstract: Abstract. Camellia japonica L. (Theaceae), an insect-and bird-pollinated, broad-leaved evergreen tree, is widely distributed in Japan and the southern Korean peninsula. The species has a relatively even age distribution within populations, which may influence the spatial genetic structure of different age classes relative to species with typical L-shaped age distributions. To determine whether the internal spatial genetic structure found in seedlings and young individuals carries over into adults, we used allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
114
2
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(126 citation statements)
references
References 78 publications
(114 reference statements)
7
114
2
3
Order By: Relevance
“…It further indicates that the extent of gene flow is large for all life stages, and that no historic events have led to a fundamental alteration of processes across life stages. This is in line with other studies that have also shown that genetic diversity is similar across life stages within populations (for example, Chung et al, 2003;Jacquemyn et al, 2006). The levels of genetic diversity in our study were similar to those of another study on P. africana in Kakamega Forest (Farwig et al, 2008) and to those of European Prunus species (Stoeckel et al, 2006, P. avium: H e : 0.448-0.918) but higher than the diversity in an Asian Prunus species (Pakkad et al, 2003, P. cerasoides: H e : 0.292-0.689).…”
Section: Inbreeding and Genetic Diversitysupporting
confidence: 93%
See 3 more Smart Citations
“…It further indicates that the extent of gene flow is large for all life stages, and that no historic events have led to a fundamental alteration of processes across life stages. This is in line with other studies that have also shown that genetic diversity is similar across life stages within populations (for example, Chung et al, 2003;Jacquemyn et al, 2006). The levels of genetic diversity in our study were similar to those of another study on P. africana in Kakamega Forest (Farwig et al, 2008) and to those of European Prunus species (Stoeckel et al, 2006, P. avium: H e : 0.448-0.918) but higher than the diversity in an Asian Prunus species (Pakkad et al, 2003, P. cerasoides: H e : 0.292-0.689).…”
Section: Inbreeding and Genetic Diversitysupporting
confidence: 93%
“…Restricted gene flow is probably one of the most prevalent factors influencing fine-scale spatial genetic structure (SGS), that is, a decrease in relatedness with increasing spatial distance between individuals (Vekemans and Hardy, 2004). It results in spatial aggregations of siblings in close vicinity of the mother trees and, thus, in high offspring's SGS (for example, Chung et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in some respects this may be similar to what occurs across life stages in populations that have strong intraspecific competition (although it should be noted that N e would also be decreasing in many cases). It has been observed in many tree species that relatively large amounts of autocorrelation are found in seedlings, less in juveniles and still less in reproductive adults and older age classes (Epperson and Alvarez-Buylla, 1997;Chung et al, 2003).…”
Section: Bk Eppersonmentioning
confidence: 99%